Stage- and tissue-specific expression of two homeo box genes in sea urchin embryos and adults. - Dolecki, G J (1988)
We report the isolation of two different homeo box genes, HB3 and HB4, from the Hawaiian sea urchin Tripneustes gratilla. DNA sequencing revealed a definitive Antennapedia (Antp) class homeo box in each gene. Southern transfer hybridizations showed the genes to be single-copy. A 5.7-kb transcript of the HB3 gene was found in ovary, testis, small intestine and gastrula poly(A)+ RNA. The HB4 gene produces three transcripts. A 3.7-kb and a 4.4-kb transcript are expressed during embryogenesis. A 3.5-kb transcript appears in each of the adult tissues studied. The HB4 gene appears to be the sea urchin cognate of the Drosophila infrabdominal-7 (iab-7) gene, the mouse Hox 1.7 and Hox 3.2 genes and the Xenopus X1Hbox 6 gene. An examination of Antp class homeo box genes in deuterostomes indicates that a chromosomal duplication has taken place in the evolutionary line leading to the vertebrates after the divergence of the echinoderms. Thus, the sea urchin represents the primitive condition.